The Influence of Leadership Style and Work Motivation on Employee Performance at PT. Nurmadinah, Botto Village, Campalagian District (International Journal of Economics and Management Research, 2026)
This study aims to analyze the influence of leadership style and work motivation on employee performance at PT. Nurmadinah located in Botto Village, Campalagian District. This study uses a quantitative approach with a survey method. The study population was all 100 employees of PT. Nurmadinah, and a saturated sampling technique was used so that the entire population became the sample. Data were collected through a questionnaire with a Likert scale of 1-5 and analyzed using descriptive statistics, instrument tests, classical assumption tests, and multiple linear regression analysis. The results of the study indicate that: (1) leadership style has a positive and significant effect on employee performance, (2) work motivation has a positive and significant effect on employee performance, and (3) simultaneously, leadership style and work motivation have a positive and significant effect on employee performance with a contribution of 54.2%. This study confirms the relevance of the grand theory of leadership and motivation in the context of local companies in rural Indonesia. The recommended managerial implications are improving the quality of exemplary leadership and strengthening the work motivation system, both intrinsic and extrinsic, to encourage optimal employee performance.